Tactile sensing and displays haptic feedback for minimally invasive surgery and robotics - Sokhanvar, Saeed (John Wiley & Sons, 2013)
Comprehensively covers the key technologies for the development of tactile perception in minimally invasive surgery Covering the timely topic of tactile sensing and display in minimally invasive and robotic surgery, this book comprehensively explores new techniques which could dramatically reduce the need for invasive procedures.